To a Golden Land - Greenblatt, Samuel Shlomo (My University, 2006)
The story of the Jewish community in South Africa is a long and colourful one. The population is based entirely on immigrants who first began arriving in the late 1860s. Their presence in the country is characterised by a disproportionate visibility and as being distinct from other “Diaspora” communities. The community has shrunk by a third in the last thirty years, in a mirror image of the initial waves of immigrants to the country a century before. This sense of movement spanning a long period of time in the context of the historical phenomenon that is South African Jewry suggests itself to a documentary film. A cinematic treatment of the phenomenon of waves of Jewish immigration to and from South Africa requires approaching the subject matter from a number of directions simultaneously. The film genre “historical documentary” requires equal emphasis on the techniques of cinema as well as an historical approach. This document addresses each in turn, with Section 1 dealing with the historical framework underlying the film. Section 2 addresses the theory and practice of documentary film inasmuch as it pertains to the proposed film. This section also contains a review of existing film documentary approaches to the subject matter. Section 3 contains a scene by scene breakdown of the film. The appendix contains a literature review and supplemental notes. Overall Aim The starting point for the construction of the film is an attempt to develop an approach that deliberately eschews the conventional documentary technique used in the making of similar films. By ignoring the fact that film is a predominantly visual medium, films often fall into a trap of “over-textualising” i.e. their visual or metaphorical essence becomes subordinate to the text of the film. Since the text drives the narrative, this can result in a sapping of visual interest in favour of what is often a tedious voice-over. This film wishes to take advantage of film as a rich visual and symbolic medium. I aim to show that this approach need not lead to a loss of overall transmitted content, historical or otherwise. The maxim “less is more”, though seemingly cliché, applies in large part to the making of a historical documentary.
Student Number : 8238599 - MA dissertation - School of Social Sciences - Faculty of Humanities
Keywords: Jewish community; South Africa